2019
DOI: 10.1093/eurheartj/ehz748.0587
|View full text |Cite
|
Sign up to set email alerts
|

P1835Application of SYNTAX score I, II and residual SYNTAX as predictors of long-term clinical outcomes after coronary artery bypass grafting

Abstract: Background The evaluation of coronary disease by SYNTAX score I (SSI) is used to grade coronary complexity. Following SSI, two other scores were developed: SYNTAX score II (SSII) and residual SYNTAX score (rSS). Nevertheless, there is still a lack of evidence about the prognostic significance of these scores among patients undergoing CABG. Purpose Our aim was to evaluate the relation of the SSI, SSII and rSS score with outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our study found that after 182 patients with coronary heart disease undergoing PCI treatment were classified into low-risk, medium-risk, and high-risk groups based on SYNTAX score and SYNTAX score II, the incidence of MACCE was 6.7%, 18.3%, 24.2%; 26.7%, and there are statistical differences between the groups, consistent with previous results (Sinning et al, 2013;Martins et al, 2019), suggesting that the SYNTAX score and SYNTAX score II can be used as a risk score tool for coronary heart disease patients after PCI and predict MACCR incidence. However, this study did not find a significant statistical difference in the incidence of MACCE between different groups of coronary calcium scores.…”
Section: Discussionsupporting
confidence: 91%
“…Our study found that after 182 patients with coronary heart disease undergoing PCI treatment were classified into low-risk, medium-risk, and high-risk groups based on SYNTAX score and SYNTAX score II, the incidence of MACCE was 6.7%, 18.3%, 24.2%; 26.7%, and there are statistical differences between the groups, consistent with previous results (Sinning et al, 2013;Martins et al, 2019), suggesting that the SYNTAX score and SYNTAX score II can be used as a risk score tool for coronary heart disease patients after PCI and predict MACCR incidence. However, this study did not find a significant statistical difference in the incidence of MACCE between different groups of coronary calcium scores.…”
Section: Discussionsupporting
confidence: 91%